2012
DOI: 10.1177/0091270010391789
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Eslicarbazepine Acetate on Cardiac Repolarization in a Thorough QT/QTc Study

Abstract: This study investigated the effect of eslicarbazepine acetate (ESL) on cardiac repolarization in healthy adult volunteers. A randomized, placebo/active-controlled, 4-period crossover study was conducted in 67 participants. In 3 periods, participants received once-daily doses of ESL 1200 mg, ESL 2400 mg, and placebo for 5 days; in 1 period, participants received placebo on days 1 to 4 and a 400-mg moxifloxacin single dose on day 5. In each period, 24-hour 12-lead Holter monitoring was performed on days -;1 (bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Though the reported incidence is low, treatment with some AEDs may lead to ECG morphologic changes, including lengthening of QRS duration and PR interval prolongation. [11][12][13] The vigabatrin doses used in this study, including the supratherapeutic dose that is occasionally used clinically, did not affect ECG morphology. The lack of effects on QT and QRS is consistent with most other AEDs with varying mechanisms of action.…”
Section: Discussionmentioning
confidence: 70%
“…Though the reported incidence is low, treatment with some AEDs may lead to ECG morphologic changes, including lengthening of QRS duration and PR interval prolongation. [11][12][13] The vigabatrin doses used in this study, including the supratherapeutic dose that is occasionally used clinically, did not affect ECG morphology. The lack of effects on QT and QRS is consistent with most other AEDs with varying mechanisms of action.…”
Section: Discussionmentioning
confidence: 70%
“…To give an overview of previous studies, the incidence of AEs is dose dependent and patients are more susceptible during the early phase of treatment (Table 1). From a clinical point of view and when compared with CBZ or OXC, ESL was associated with very few psychiatric events, the incidence of rash was low (<2%) and no safety concerns arising from hyponatraemia or dyslipidaemia, as well as from changes in body weight or cardiac homeostasis (e.g., QT changes), were found [17,[30][31][32]40].…”
Section: Conclusion and Expert Commentarymentioning
confidence: 98%
“…In 2011, Vaz-da-Silva et al published a study on possible effects of ESL on cardiac repolarization and concluded that even high doses of ESL (1200 and 2400 mg) did not induce clinically-relevant prolongation of corrected QT intervals in 67 healthy adult volunteers [40].…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…Several studies have clearly established the inhibition of neuronal VGSCs (Na v 1.1, Na v 1.2, Na v 1.3, Na v 1.6, Na v 1.7 and Na v 1.8) by ESL and its active metabolite S-Lic (10,20,24,41). Given that ESL prolongs the PR interval (27), potentially via inhibiting the cardiac Na v 1.5 isoform, together with the interest in inhibiting Na v 1.5 in carcinoma cells to reduce invasion and metastasis (33,34,(42)(43)(44), it is also relevant to evaluate the electrophysiological effects of ESL and S-Lic on this isoform. We therefore evaluated the effect of both compounds on Na v 1.5 current properties using whole-cell patch clamp recording, employing a two-pronged approach: (1) recording Na v 1.5 currents endogenously expressed in the MDA-MB-231 breast cancer cell line (29,30,45), and (2) recording from Na v 1.5 stably over-expressed in HEK-293 cells (HEK-Na v 1.5) (46).…”
Section: Effect Of Eslicarbazepine Acetate and S-licarbazepine On Tramentioning
confidence: 99%
“…In healthy volunteers, ESL has not been associated with cardiotoxicity and the QT interval remains unchanged on treatment (27). However, a prolongation of the PR interval has been observed (27), suggesting that caution should be exercised in patients with cardiac conduction abnormalities (13).…”
Section: Introductionmentioning
confidence: 99%